Predictors of clinical outcome after mitral valve replacement - Shweta Shende; Sushrut Potwar; Kanak Nagle; Rahul Nathani; Amit Karad (International Journal of Medical Research and Review, 2018)
Background: To identify and study predictors of morbidity, mortality, and survival after mitral valve replacement.Methods: We have examined 186 patients undergoing isolated mitral valve surgery between January 2013 to January 2015, with respect to preoperative clinical features, echocardiographic findings, hemodynamics and surgical approaches. Coronary angiography was done as a routine in all patients above 40 yrs of age & coronary artery bypass grafting with mitral valve replacement was done in 7 patients. The operative mortality was 5.37%. Postoperatively patients were followed up at 3 months interval for first 1 year & at 6 months interval thereafter.Results: Multivariate statistical analysis demonstrated that patients age > 60 years, patients with symptoms NYHA Class–IV, ventricular arrhythmias, associated disease (Coronary artery disease, Infective endocarditis), end diastolic diameter measuring ≥60 ± 10mm, left atrial Dimension ≥ 65 mm, chordal preservation (Partial / Total) independently influenced the morbidity and Mortality.Conclusion: Strategies to diminish operative mortality should include careful assessment of the risks factors in elderly patients, early operative intervention before deterioration that necessitates urgent surgery, and use of improved techniques of myocardial protection in high-risk patients.